Preliminary Assessment of Finnish Railway Bridges : Railway Infrastructure Upgrading with Increase of Axle loads from 25 to 30 tonnes on the Line Tornio - Kolari, A Comparison with Swedish Railway Bridges on the Lines Luleå - Narvik and Haparanda - Boden - Elfgren, Lennart; Enochsson, Ola; Puurula, Arto; Nilimaa, Jonny; Töyrä, Björn (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2009)
Some 60 bridges on the Finnish Railway Line between Tornio and Kolari have been assessed in a preliminary way. The study is based on experiences on the two neighbouring Swedish Railway Lines Malmbanan and Haparandabanan. Godkänd; 2009; Bibliografisk uppgift: Published by Lulea Railway Research Centre (JVTC) and Division of Structural Engineering at Luleå University of Technology; 20150411 (elfgren)